SEASONAL OCCURRENCE OF PASTEURELLOSIS IN RABBITS - N.A. Nabieva (Scholar Express Journals, 2024)
As a result of scientific research, it was found that rabbit pasteurellosis occurs in the regions of Samarkand region as a result of epizootic analysis. Among the 4 seasons of the year, it was found that the number of pasteurellosis was found in rabbits in spring, and it was found that 43% of pasteurellosis was recorded in the spring when compared to the infected rabbits on farms.
Keywords: rabbit; pasteurellosis; district; season